Implemantasi Kebijakan Pemerintah Kota Denpasar Perwali No. 36 Tahun 2018 Tentang Pengurangan Penggunaan Kantong Plastik - Syntia Dewi, Ni Luh Putu; -, Bandiyah; Noak, Piers Andreas (Jurnal Nawala Politika, 2021)
This study aims to find out how the implementation of the mayor's regulation of Denpasar No. 36 of 2018 concerning Reducing the Use of Plastic Bags in Denpasar City. This research is dissected using the theory of policy implementation by Merilee S. This approach can describe the political process, namely through the decision-making process carried out by various influential actors, while the administrative process can be seen through the general process of administrative action. This study uses a descriptive qualitative research methodology in explaining the form of data. The results show that there are several phenomena such as the existence of companies and traders who still ignore this regulation, the sanctions given are still not giving a deterrent effect because the sanctions are still in the form of reprimands, thirdly the lack of socialization and massive supervision from the government. Keywords: Implementation, Public Policy, Plastic Waste,